Analisis Perbandingan Sentimen Pengguna iPusnas dan JakLITera dengan Algoritma SentiWordNet - Hendrayani, Putri Fajar Ayu; Rahmi, Rahmi (UI Scholars Hub, 2025)
iPusnas and JakLITera are two national digital library applications developed to enhance public access to literacy in Indonesia. This study compares user perceptions of both applications through sentiment analysis using the SentiWordNet (Sentiment WordNet) algorithm, implemented in Orange data mining software. The dataset comprises user comments from the Google Play Store, collected between 2023 and 2025. A qualitative, lexicon-based method was applied to classify sentiments into positive, neutral, and negative categories. Results show that iPusnas is dominated by negative sentiment (47%), mainly due to technical issues such as bugs, login failures, and slow performance. In contrast, JakLITera received 55% positive sentiment, largely due to the ease of reservation features, although OTP verification issues remain. The findings indicate that iPusnas is dominated by negative sentiment due to technical issues such as login failures and slow loading times, despite its strength in providing a wide range of digital collections. In contrast, JakLITera demonstrates relatively more positive responses owing to the efficiency of its reservation feature, although it remains constrained by account verification problems and limited collections.